Foreign Direct Investment in Latin America and the Caribbean 2016 - Economic Commission for Latin America; the Caribbean (United Nations, 2016)
In its latest edition, the Foreign Direct Investment in Latin America and the Caribbean report analyzes in-depth the FDI received by the Caribbean, where these flows are much more significant than in the rest of the region as a proportion of Gross Domestic Product (GDP). The study also examines the impact of FDI on the environment, which has not been measured or regulated sufficiently by countries in the region.